Dinamika Hubungan Antara Birokrasi Dan Kekuasaan Politik - Mozin, Sri Yulianty; Sulila, Vivi Venti Vera; Bangko, Nia Rahmadani (JPS: Journal of Publicness Studies, 2025)
This study analyzes the relationship between power structures and bureaucratic hierarchy within Indonesia’s political governance. It focuses on how political power affects bureaucratic professionalism, neutrality, and effectiveness. Using a literature review method, the study examines 15 national publications from 2020-2025 discussing bureaucratic politicization, civil service neutrality, and institutional reform. The analysis applies content analysis with thematic grouping. Findings reveal that bureaucracy remains vulnerable to political intervention and patronage, reducing its independence and performance. However, the application of a merit system and stronger neutrality regulations are strategic measures toward a professional and accountable bureaucracy. The study highlights the importance of balancing political power and bureaucratic autonomy to achieve adaptive and public-oriented governance.